A C-F-L condition for the gravity wave and the inertial-gravity waves using an Arakawa D lattice - Demmler, M. I.; Camerlengo, A. L.; M. S., M. Zaki; Husain, M. L. (Malaysian Journal of Science, 1995)
The Courant Friedrichs-Levy stability condition for Arakawa's D lattice has been derived. The stability condition for this particular grid is less restrictive than the stability condition for grids A and C.